2016
DOI: 10.1016/j.aogh.2015.12.013
|View full text |Cite
|
Sign up to set email alerts
|

State-of-the-Art Review on Diabetes Care in Italy

Abstract: In Italy, diabetes affects more than 3.5 million people, about 5.5% of the general population.1 In the last 20 years, the number of Italians with diabetes has increased by about 60%, from only 3.4% in 1993.1-3 As a result of these epidemic proportions, the Italian Health Service estimates spending about V10 billion ($US 11 billion) yearly for direct and indirect costs related to diabetes care. 4 This relative increase in expenditure is, at least in part, due to the increase of the mean lifetime expectancy obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 20 publications
0
12
1
Order By: Relevance
“…By contrast, HbA1c in N Europe was lower when insulin was started (though still poor) and decreased the smallest amount despite reasonable insulin dosage, perhaps suggesting the gain in control here was to a greater extent due to the insulin rather than improved patient education and motivation. Although there were marked differences in type of physician involved in starting insulin between the regions (Table 1), these reflect some known factors such as the high number of diabetologist specialists in Italy, the long-standing predominance of women as specialists in ex-Soviet countries and differences in structure of care in individual countries in Europe, with no regional pattern [13,14]. Therefore it does not seem possible to attribute differences in baseline characteristics or care provided when starting insulin to physician characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, HbA1c in N Europe was lower when insulin was started (though still poor) and decreased the smallest amount despite reasonable insulin dosage, perhaps suggesting the gain in control here was to a greater extent due to the insulin rather than improved patient education and motivation. Although there were marked differences in type of physician involved in starting insulin between the regions (Table 1), these reflect some known factors such as the high number of diabetologist specialists in Italy, the long-standing predominance of women as specialists in ex-Soviet countries and differences in structure of care in individual countries in Europe, with no regional pattern [13,14]. Therefore it does not seem possible to attribute differences in baseline characteristics or care provided when starting insulin to physician characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…Participants with T2D who were not receiving medication treatment were required to provide a knowledgeable description of diabetes diagnosis, symptoms, and treatment that clearly indicated they were honestly reporting their diagnosis. During patient recruitment, efforts were made to ensure that the ratio of T1D to T2D would be roughly similar to the ratio worldwide and in Italy (i.e., approximately 90% T2D) [36,37].…”
Section: Participantsmentioning
confidence: 99%
“…The incidence of T1DM has progressively increased in Italy with 3-4 times higher rates in Sardinia than in other parts of Italy [8, 9]. The Italian Health Service system estimates that 10 billion euros is the annual cost for the care of patients with DM, and these costs are increasing over time [10, 11]. …”
Section: Diabetes Mellitus: the Italian Scenariomentioning
confidence: 99%
“…In Italy, there are no national data about prevalence and incidence of legal blindness due to DR, and there is no national registry of patients with DM [11]. However, several studies reported the prevalence and incidence of DR from geographically limited population-based studies [1820].…”
Section: Diabetic Retinopathy: Global and Italian Epidemiology Datamentioning
confidence: 99%